Paratopia política e formação do ethos discursivo na atividade literária : uma análise discursiva de narrativas brasileiras - Ponsoni, Samuel (Universidade Federal de São Carlos, 2015)
Our research seeks a discursive understanding of some literary events that occurred during the last Brazilian dictatorship, that is, between 1964 and 1985, during which military and civilians perpetrated a coup to the political and democratic state of law. During this period, various cultural, social, political events were severely repressed. There was, during the most repressive years - 1970 - an institutionalized censorship, which bared subversive content to the existing order. It is precisely in this most repressive period that it is focused our research to bring literary materials for analysis of some linguistic phenomena. These materials are some texts, tale genre of Cadeiras proibidas by Ignácio de Loyola Brandão, 1976, and Seminário dos ratos, by Lygia Fagundes Telles, 1977. These materials are the corpora of the research, which were taken sets of textual sequences for analysis, foundations of some theoretical notions from a discursive viewpoint of discourse analysis, more specifically those forged in the polls and French scholars. At first, this research aims an understanding of how such literary constructions created conditions of possibility to produce, incorporate and manage discursive places of meaning, even having as historical conditions of production, a curtailed and oppressive socio-cultural environment. This time also, we want to understand how it was possible the literary creation itself, at a time of censorship and repression, by a hypothesis that is based on the notion concept of paratopia, from Dominique Maingueneau in his studies of literary discourse. To the different axes of paratopic creation, we want to add an axis specifically of political creation, which would explain a certain theoretical and analytical path to literary productions in the historic time when appeared such narratives. In a second step, there is a shift that aims to establish a different theoretical and methodological procedure for, in the same process, comprehend, describe and interpret linguistic elements and discursive elements of these corpora. In this second "time-purpose" it is firmed the hypothesis of scrutinizing the composition and formation of names and descriptions given to characters in their actions in the narrative plot. Moreover, as these names and descriptions are joined also to the composition of stereotypes that ultimately sustain discursive images that the characters give themselves and others, building dialectically, then, a discursive ethos of these texts for the historical and social context in question. These elements, we believe, make up the set of forms for adhesion of speakers to a desired speech by literary texts in any possible worlds. Trying to answer these questions and hypotheses are the objective of this research.
Keywords: Discurso literário; Paratopia política; Estereótipos; Ethos discursivo; Literary discourse; Political paratopie; Stereotypes; Discoursive ethos; LINGUISTICA, LETRAS E ARTES::LINGUISTICA